Mortality salience enhances neural activities related to guilt and shame when recalling the past - Xu, Zhenhua; Zhu, Ruida; Zhang, Shen; Zhang, Sihui; Liang, Zilu; Mai, Xiaoqin; Liu, Chao (Cerebral cortex, 2022)
Mortality salience (MS) influences cognition and behavior. However, its effect on emotion (especially moral emotions) and the underlying neural correlates are unclear. We investigated how MS priming modulated guilt and shame in a later recall task using functional magnetic resonance imaging. The behavioral results indicated that MS increased self-reported guilt but not shame. The neural results showed that MS strengthened neural activities related to the psychological processes of guilt and shame. Specifically, for both guilt and shame, MS increased activation in a region associated with self-referential processing (ventral medial prefrontal cortex). For guilt but not shame, MS increased the activation of regions associated with cognitive control (orbitofrontal cortex) and emotion processing (amygdala). For shame but not guilt, MS decreased brain functional connectivity related to self-referential processing. A direct comparison showed that MS more strongly decreased a functional connectivity related to self-referential processing in the shame than in the guilt condition. Additionally, the activation of insula during MS priming was partly predictive of neural activities related to guilt and shame in the subsequent recall task. Our study sheds light on the psychological and neural mechanisms of MS effects on moral emotions and provides theoretical insights for enriching terror management theory.
Online veröffentlicht: 01. Februar 2022
Gesehen am 16.02.2023